2014
DOI: 10.1007/s00216-014-7746-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative HPLC-MS analysis of nucleotide sugars in plant cells following off-line SPE sample preparation

Abstract: An analytical workflow was developed for the absolute quantification of uridine diphosphate (UDP)-sugars in plant material in order to compare their metabolism both in wild-type Arabidopsis thaliana and mutated plants (ugd2,3) possessing genetic alterations within the UDP-glucose dehydrogenase genes involved in UDP-sugar metabolism. UDP-sugars were extracted from fresh plant material by chloroform-methanol-water extraction and further purified by solid-phase extraction with a porous graphitic carbon adsorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Separation of UDP-glucose and UDP-galactose was achieved according to a method described by Behmüller et al (62) using an Agilent 1100 quaternary HPLC system equipped with a HYPERCARB 150-mm by 1-mm column (Thermo Scientific) at a temperature of 60°C, a flow rate of 0.1 ml/min with a gradient of A (water), B (water-0.3% formic acid [pH adjusted to 9 using NH 3 ; aqueous]), C (acetonitrile), and D (79.95% acetonitrile-19.95% water-0.1% TFA). The gradient is shown in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Separation of UDP-glucose and UDP-galactose was achieved according to a method described by Behmüller et al (62) using an Agilent 1100 quaternary HPLC system equipped with a HYPERCARB 150-mm by 1-mm column (Thermo Scientific) at a temperature of 60°C, a flow rate of 0.1 ml/min with a gradient of A (water), B (water-0.3% formic acid [pH adjusted to 9 using NH 3 ; aqueous]), C (acetonitrile), and D (79.95% acetonitrile-19.95% water-0.1% TFA). The gradient is shown in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…The extracts were combined, dried with a centrifugal vacuum concentrator, and resuspended in 1 mL of water. Solid-phase extraction with Supelclean ENVI-Carb SPE tubes (Sigma-Aldrich) was performed as described by Behmüller et al (2014). Samples were dried using a centrifugal vacuum concentrator, resuspended in 500 mL of water, and analyzed immediately.…”
Section: Ndp-sugar Analysis By Lc-ms/msmentioning
confidence: 99%
“…By contrast, we have found that the application of porous graphitic carbon a reliable and robust separation technique that is highly compatible with MS. The approach generates baseline separation of all reported plant nucleotide sugars and we have not observed the reported retention time instabilities (Behmuller, Forstenlehner, Tenhaken, & Huber, ). The stability of porous graphitic carbon we have observed over many hundreds of samples may be because we do not regenerate the column with trifluoroacetic acid, as has been reported for this technique (Pabst et al., ).…”
Section: Commentarymentioning
confidence: 79%